Impaired reading comprehension and mathematical abilities in male adolescents with average or above general intellectual abilities are associated with comorbid and future psychopathology - Weiser, Mark; Reichenberg, Abraham; Rabinowitz, Jonathan; Nahon, Daniella; Kravitz, Efrat; Lubin, Gad; Knobler, Haim Y; Davidson, Michael; Noy, Shlomo (The journal of nervous and mental disease, 2007)
Research indicates that persons with learning disorders often suffer from psychopathology. We assessed current and future psychopathology in male adolescents with discrete impairments in reading comprehension (IRC) or arithmetic abilities (IAA) but with average or above-average general intellectual abilities. Subjects were a population-based cohort of 174,994 male adolescents screened by the Israeli Draft Board with average or above-average intellectual abilities but with low scores (8.6th and 10th lowest percentile respectively) on reading or arithmetic tests. They were compared with adolescents who scored in the 10th percentile and above on these tests (comparison group). Relative to the comparison group, male adolescents with IRC, IAA, or IRC and IAA (0.69%), had poorer scores on most behavioral assessments and higher prevalence of current psychopathology: 4.2% (comparison group), 8.0% (IRC), 7.0% (IAA), and 9.8% (IRC and IAA). Adolescents with IRC were also at increased risk for later hospitalization for schizophrenia (hazard ratios = 1.8, 95% confidence interval: 1.3-2.6). Male adolescents with average and above-average general intellectual abilities but with IRC or IAA are more likely to have current and future psychopathology. Impairments in intellectual functioning and abnormal behaviors leading to mental illnesses may share common neurobiological substrates. The results support screening male adolescents with learning disorders for psychopathology.